2018
DOI: 10.1007/s11135-018-0814-6
|View full text |Cite
|
Sign up to set email alerts
|

Recursive residuals for linear mixed models

Abstract: This paper presents and extends the concept of recursive residuals and their estimation to an important class of statistical models, Linear Mixed Models (LMM). Recurrence formulae are developed and recursive residuals are defined. Recursive computable expressions are also developed for the model's likelihood, together with its derivative and information matrix. The theoretical framework for developing recursive residuals and their estimation for LMM varies with the estimation method used, such as the fitting-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Our data consists of countryyear observations, which justify the use of panel data techniques and a significant Hausman-test confirmed the use of the fixed-effect model. The models are then assessed using standard model diagnostic tools based on residual and recursive residuals in checking the model assumptions (Bani-Mustafa et al, 2019).The results of our panel regression related to the old members before and after the enlargement are summarized in Table 5. The regression results presented in Column 1confirmed our fourth hypothesis and showed a negative and significant relationship between public governance score and tax evasion behavior in old members in both periods: before and after the EU enlargement.…”
Section: Regression Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data consists of countryyear observations, which justify the use of panel data techniques and a significant Hausman-test confirmed the use of the fixed-effect model. The models are then assessed using standard model diagnostic tools based on residual and recursive residuals in checking the model assumptions (Bani-Mustafa et al, 2019).The results of our panel regression related to the old members before and after the enlargement are summarized in Table 5. The regression results presented in Column 1confirmed our fourth hypothesis and showed a negative and significant relationship between public governance score and tax evasion behavior in old members in both periods: before and after the EU enlargement.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Our data consists of country-year observations, which justify the use of panel data techniques and a significant Hausman-test confirmed the use of the fixed-effect model. The models are then assessed using standard model diagnostic tools based on residual and recursive residuals in checking the model assumptions (Bani-Mustafa et al , 2019). The results of our panel regression related to the old members before and after the enlargement are summarized in Table 5.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Descriptive statistics involved frequencies and percentages for categorical variables, and one-way analysis of variance (ANOVA) was used to assess differences among the SMEs groups subject to the sociodemographic data of the businesses. Furthermore, the goodness of fit and model validity and adequacy were checked using residuals and recursive residuals [57]. Correlation analysis was performed to understand the relationships between constructs and the dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Internal consistency refers to the degree to which all items on a particular test measure the same attribute. Cronbach α coefficient is 0.88, which is higher than 0.7; it can be considered that this dimension's internal consistency and stability has been achieved [57][58][59].…”
Section: Challenges Facing the Smes During Covid-19 And Potential Solutionsmentioning
confidence: 99%
“…Coal seams have a maximum fraction of micropores or transition pores on their internal as well as external surface and gas flow in micropores is governed by Fick's law but in the case of mesopores or macropores research has shown that the gas movement is governed by Darcy law [ 77 ]. established a model for gas flow based on crystal, surface, transitional, Knudsen, and Fick's diffusion and concluded them as the main gas flow patterns in coal seams and large variations have been reported in calculations of values by Fick's model [ 78 , 79 ]. The next section describes the different gas flow models proposed.…”
Section: Gas Flow Behavior In Coalmentioning
confidence: 99%